An expanded ND2 phylogeny of the brookii and prashadi groups with the description of three new Indian Hemidactylus Oken (Squamata: Gekkonidae) - Agarwal, Ishan; Bauer, Aaron M.; Giri, Varad B.; Khandekar, Akshay (Zootaxa, 2019)
We present an expanded ND2 phylogeny of the brookii and prashadi groups of Indian Hemidactylus. While relationships within the clades are not well resolved, we recover many well supported subclades and a number of deeply divergent lineages within each clade. We use morphological data to describe three of these divergent lineages as new species; Hemidactylus kolliensis sp. nov., a member of the prashadi group from high elevation in the Kollimalai Massif in Tamil Nadu, Hemidactylus chikhaldaraensis sp. nov. and Hemidactylus sankariensis sp. nov., both members of the brookii group, are described from high elevation of the Satpuras in Maharashtra and low elevation of Tamil Nadu, respectively. The three new species exhibit >15% divergence for the ND2 gene from their phylogenetic sisters and differ in a number of morphological characters from all Indian congeners. The discovery of three more endemic Hemidactylus species from rocky habitats suggests that many more remain to be discovered across India.